Self Care Management of Hypertensive Patients in Pangarangan Village Sumenep City District, Sumenep Regency - Emdat Suprayitno; Cory Nelia Damayanti (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
ABSTRACT Hypertension is a major risk factor for cardiovascular disease death which is a cause of genetic, environmental and social factors. Elderly people with hypertension have difficulty doing self-care management on themselves, which can worsen their quality of life. The purpose of this study was to determine self-care management of hypertensive patients. This study is a descriptive using a non-analytic cross-sectional design. The population were 66 patients with hypertension in Pangarangan Village, Sumenep Regency with total sampling. The research instrument was a questionnaire of Hypertension Self Management Behavior Questionnaire. The results indicate the majority of self-care management in elderly people with hypertension is sufficient arround 41 respondents (62.1%). The elderly people with hypertension are expected to improve their self-care independence during home care with better self-care management. Key Words: Hipertension, Self Care, Self Care Management